Fluorescência da clorofila a em diferentes fases do desenvolvimento e qualidade dos frutos de três genótipos do maracujazeiro cultivados no norte do Estado do Espírito Santo - Valbão, Sigrid Costa (2009)
The objective of this work was to study the chlorophyll a fluorescence emission kinetics of three passion fruit genotypes cultivated on adverse conditions in the north of Espírito Santo; and its association with the quality of the fruits. Two of the three studied genotypes are commercially known: FB 100 (Maguary) and FB 200 (Yellow Master). The third one presents purplish skin, suitable for the in nature fruits exportation marketing, in this work it is called test genotype – GT. The plants were cultivated in an experimental field of the Instituto Capixaba de Assistência Técnica e Extensão Rural (INCAPER), in Sooretama, ES, and submitted to four field treatment: 1= plowing and harrowing; 2= plowing, harrowing andsubsoiling; 3= plowing, harrowing and ridge; 4= plowing, harrowing, subsoiling and ridge. The chlorophyll a kinetics emission was measures monthly, since the seedlingsproduction stage until the fruits production stage, using a portable Fluorometer (Handy PEA - Hanstech, UK). The photochemical efficiency of the three genotypes was better when the plantules were in the nursery. In the nursery to field transition, the Maguary genotype was evidenced for a larger quantum output of energy conversion (FV/F0), more probability (in zero time) of a captured excitron by the photosystem II (PSII) reaction center (RC) to move an electron in the chamber transport to beyond than QA- (ET0/TR0) and a higher performance index (P.I), when compared with Yellow Master and GT genotypes. When the plants were transferred to the field, the GT genotype seedlings presented lower values of ET0/TR0 and of P.I. The fluorescence parameters turned evident the stress that those seedlings suffered when the transplantation occurred between the nursery and the field and on the vegetative growing to the reproductive growing change. In the vegetative phase to the reproductive phase transition, the photosystem II (PSII) maximum quantum efficiency (FV/FM), the radiant energy absorption flow per reaction center (ABS/RC), the reaction of the captured energy in zero time (TR0/RC), and the electron transportation flow per reaction center in zero time (ET0/RC), were similar in the three genotypes. However, the GT genotype showed a higher PSII effective maximum quantum yield (FV/F0) and high performance index (P.I), probably because the absorbed energy dissipation (DI0/RC) was smaller. The average rate among chlorophyll/carotenoid was, statistically, higher in GT genotype than those that were found in FB 100 (Maguary) and FB 200 (Yellow Master) genotypes during the transition from vegetative to reproductive stage, which turns evident the chlorophyll b and carotenoids pigments importance in the photoprotection of the photosystem that were directly related to the superior performance index (P.I.). The analysis of the soluble solids (SS) and titratable acidity (AT) of the three genotypes of the passion fruit were made using a direct reading of the juice with a digital refractometer (Instrutherm, mod. RTD-45) and titration with NaOH 0,1 N (default), respectively. The results showed that, in a plowed, harrowed, subsoiling and ridge field (treatment number 4) the FB100 and FB200 cultivars showed a SS/AT rate average among 2,8 to 3,7 as long as in GT the average rate was 2,6. In spite of the excellent physiological and agronomical characteristics, these results represent a superior tasteto in nature consume in the two cultivars that are already established in the state of Espírito Santo.